Fingermark visualisation on thermal paper – A comparison among different procedures as an outcome of the 2018 collaborative exercise of the ENFSI Fingerprint Working Group. (November 2020) - Zampa, F.; Hilgert, M.; Mattei, A.
Highlights: A collaborative exercise was carried out in 2018 within ENFSI EFP-WG. The visualisation test was focused on thermal paper. The preliminary inspection is highly advisable. The use of a sequential procedure is highly recommended. Data does not support the use of superglue, powders, iodine. Abstract: In 2018 the Fingerprint Working Group (EFP-WG) of the European Network of Forensic Science Institutes (ENFSI) undertook a collaborative exercise (CE) with the aim of assessing the ability in developing fingermarks on an item constituted of a thermal layer. The test was prepared and managed by the officially established advisory group. The characteristics of the CE are summarised. Different approaches emerged from the outcomes showing on average valid results. What is evident from data is that the preliminary inspection is highly advisable especially for the thermal side exploiting specific combinations of wavelengths and filters. In general, better performances were achieved by laboratories using multiple processing techniques. Conversely, few laboratories were capable to reach the expected results with only one step process. Finally, data does not support the use of cyanoacrylate, powders, and iodine on this specific substrate.